2021
DOI: 10.3390/medicina57101086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Process and Outcomes in Patients after Coronavirus Infection 2019 Outbreak

Abstract: Background and Objectives: The coronavirus infection 2019 (COVID-19) pandemic has affected emergency department (ED) management. Its viral transmission necessitates the use of isolation rooms and personal protective equipment for treating suspected patients, such as those with fever. This delays the time until the first encounter with the patients, thereby increasing the length of stay (LOS) in the ED. We aimed to compare delays in the ED LOS and clinical processes between the COVID-19 period and pre-COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Moreover, our study showed that the pandemic changed the morbidity of emergency general surgeries performed. More specifically, the number of digestive surgeries (19.7% vs. 16.4%), hernia repair surgeries (22.6 vs. 18.6%), and of soft tissue infection surgeries (28.3% vs. 26%) decreased, while hepatobiliary surgeries (21.7% vs. 30.5%) and orthopedic surgeries (7.7% vs. 8.5%) increased.On the one hand, a main hypothesis that can explain the decrease in some types of surgery during the pandemic, such as soft tissue infection surgeries, is that patients delayed going to the surgery department to avoid possible COVID-19 infection [21][22][23]. This delay may translate into a more advanced level of disease [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our study showed that the pandemic changed the morbidity of emergency general surgeries performed. More specifically, the number of digestive surgeries (19.7% vs. 16.4%), hernia repair surgeries (22.6 vs. 18.6%), and of soft tissue infection surgeries (28.3% vs. 26%) decreased, while hepatobiliary surgeries (21.7% vs. 30.5%) and orthopedic surgeries (7.7% vs. 8.5%) increased.On the one hand, a main hypothesis that can explain the decrease in some types of surgery during the pandemic, such as soft tissue infection surgeries, is that patients delayed going to the surgery department to avoid possible COVID-19 infection [21][22][23]. This delay may translate into a more advanced level of disease [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…Bae et al confirmed that the overall length of ED stays of fever patients increased from before to after the onset of the COVID-19 pandemic [22], and the ED stay duration of septic shock patients increased significantly after the onset of the COVID-19 pandemic (pre-COVID-19 pandemic: 5.0 ± 2.3 h vs. post-onset of the COVID-19 pandemic: 5.9 ± 3.0 h; p = 0.015). These authors also concluded that the time to antibiotic administration significantly increased for pyrexic patients who visited the ED; however, in the present study, the time to antibiotic administration did not increase in severely ill patients with septic shock (2.4 ± 1.6 h vs. 2.2 ± 1.3 h; p = 0.288) [22]. In addition, the present study did not investigate the effects of delayed CT exam or interventions.…”
Section: Discussionmentioning
confidence: 95%
“…The measures to prevent the spread of COVID-19 infection, including social distancing measures, hand washing, wearing a mask, and school closures, helped prevent the transmission of respiratory diseases [ 22 ]. Furthermore, because patients suspected of having the COVID-19 infection, such as those with fever or respiratory symptoms, used isolation rooms during the COVID-19 period, the number of patients that could be accommodated in the ED was inevitably reduced [ 24 ]. On the other hand, the proportion of admissions to the general ward decreased in the COVID-19 period for all age groups, except for the 13–17 years group; this finding may be associated with the decrease in the number of patients with respiratory diseases, considering that patients with respiratory complaints reportedly have a high risk of admission on revisit according to previous studies [ 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 period, the number of pediatric patients visiting the ED decreased. Particularly patients with respiratory and infectious diseases and low acuity had a short length of stay (LOS) in the ED [ 22 , 23 ], while those with fever had a prolonged stay [ 24 ]. Furthermore, the management strategies for pediatric patients with trauma also changed [ 25 ].…”
Section: Introductionmentioning
confidence: 99%